Serum Endothelin-1 Level >2.0 pg/mL associates with High-Risk Duke Treadmill Score among Chronic Coronary Syndrome Patients - Muhammad Sarwansyah Putra; Irsad Andi Arso; Ira Puspitawati; Anggoro Budi Hartopo (Jurnal Kardiologi Indonesia, 2026)
Background: Chronic coronary syndrome (CCS) contributes to morbidity and increased risk of acute coronary syndrome within 5 years. Duke Treadmill Score (DTS) is the most robust risk stratification based on cardiac exercise stress test, which predicts 5-year survival. Those with high-risk DTS (DTS ≤11) had the least favorable survival. Endothelin-1, a potent vasoconstrictor peptide, affects the 5-year survival in CCS. This study aimed to investigate the association between serum endothelin-1 level and DTS risk stratification among Indonesian patients with CCS. Methods: This was a cross-sectional study that recruited consecutive patients with CCS after Coronary Angiography (CAG). The DTS data were collected from the previous Treadmill Test (TMT) and were classified into high-risk DTS (DTS ≤-11) and low-moderate-risk DTS (DTS >-11). A serum sample for measuring endothelin-1 was withdrawn during CAG and used in the ELISA protocol. A high endothelin-1 level was defined as > 2.0 pg/mL. An association between variables was assessed using statistical analysis (significance at p < 0.05). Results: Eighty subjects were enrolled. Median time interval of TMT and endothelin-1 measurement was 30 days. Mean age was 58.48±8.73 years old, with males predominant (82.5%). Hypertension (71.3%) and previous Acute Coronary Syndrome (ACS) (52.5%) were dominant. The proportion of subjects with high-risk DTS was 52.5%. Median endothelin-1 level was 1.8 pg/mL (range: 0.4 - 6.8 pg/mL). Serum endothelin-1 level > 2.0 pg/mL was observed in 34 subjects (42.5%), of whom 23 (67.6%) had high-risk DTS. There was a significantly increased risk of high-risk DTS in subjects with serum endothelin-1 >2.0 pg/mL (OR 2.97; 95% CI 1.18-7.51; p=0.020). Based on bivariate analysis, two variables, namely hypertension (p=0.052) and history of ACS (p=0.036), were also significantly associated with high-risk DTS. In multivariate analysis, endothelin-1 level >2.0 pg/mL had an adjusted OR of 1.75 (95% CI: 0.60-5.13, p=0.305), indicating no statistically significant independent association with high-risk DTS. Hypertension and a history of ACS had an independent and significant association with high-risk DTS. Conclusion: Among CCS patients, serum endothelin-1 level > 2.0 pg/mL was associated with high-risk DTS from TMT examination. However, this association was not independent, as in hypertension and history of ACS.